Mucormycosis caused by Apophysomyces species: An experience from a tertiary care hospital in Western India and systematic review of global cases. Issue 3 (20th October 2022) - Samaddar, Arghadip; Shrimali, Twishi; Sharma, Anuradha
Abstract: Apophysomyces species are an emerging cause of mucormycosis in several regions of the world, primarily affecting immunocompetent individuals. The present study addresses the global epidemiology, clinical presentation, management and outcome of mucormycosis caused by Apophysomyces spp. The study included patients diagnosed with Apophysomyces infection at our hospital between March 2019 and August 2020. In addition, cases published in PubMed and Google Scholar from inception to July 2022 were systematically searched and analysed. Only proven and probable cases that meet the eligibility criteria were included. The Indian cases were compared with those from other countries, and the results were analysed by descriptive statistics. In total, six cases of mucormycosis due to Apophysomyces spp. were diagnosed at our hospital, with additional 250 cases identified through literature search. The main underlying diseases were diabetes mellitus (24%), malignancy (3.2%) and chronic kidney disease (2.8%). The major predisposing factor was trauma (55.6%). Necrotizing fasciitis was the most common (63.2%) clinical presentation. Healthcare‐associated mucormycosis accounted for 10.4% of the cases. Globally, A. elegans was the most common species (48.8%), whereas A. variabilis was predominant (86.2%) in India. Surgery was performed in 83.5% of patients. Among those treated with antifungal agents, 98% received amphotericin B and 8.1% received posaconazole. Inappropriate antifungal usage was observed in 12.7%. The overall mortality was 42.3%. A combined medical and surgical management was associated with higher survival. Our study highlights the knowledge gap among physicians regarding this infection. A timely diagnosis and aggressive management can improve the outcomes in such cases.